The effect of different dose regimens of tranexamic acid in reducing blood loss during hip surgery - Anil Kumar Thipparampall; Indira Gurajala; R Gopinath (Indian Journal of Anaesthesia, 2017)
Background and Aims: Antifibrinolytics may help bleeding in orthopaedic surgeries. The present study was undertaken to compare two dose regimens of tranexamic acid (TA) on perioperative blood loss in patients undergoing hip surgeries. Methods: In a prospective, randomised, controlled study, 59 patients scheduled for hip surgery were divided into Group C: receiving normal saline (n - 20), Group B: receiving single dose of TA (10 mg/kg) (n - 21), and Group I: receiving a bolus (10 mg/kg) plus infusion (1 mg/kg/h) of TA up to 4 h postoperatively (n - 18). Blood loss, haemoglobin and allogeneic blood transfusions were compared between the groups. For parametric data, P was calculated by ANOVA. Intergroup comparison was done by post hoc analysis with Bonferroni test. P < 0.05 was considered significant. Results: The intra-operative blood loss was lower in the patients who received TA (525 ± 150, 456 ± 156 and 400 ± 133 ml in Group C, B and I respectively; P = 0.05). The 6th hourly drain collection in Group I was lower than Group B and C (41 ± 18, 46 ± 14 and 31 ± 14 ml in Group C, B, and I respectively; P = 0.018). The blood loss at 24 h was less in groups receiving TA (146 ± 32, 120 ± 76, 107 ± 37 ml for Group C, B and I, respectively; P = 0.02). The requirement of blood transfusions was lower in Group I. Conclusions: A bolus of tranexamic acid followed by infusion is more useful than a single dose in decreasing perioperative blood loss in patients undergoing hip surgeries. It reduces allogenic blood transfusion without increasing risk of thromboembolic events.